ANALISIS MEKANISME RESTRUKTURISASI DALAM PENYELESAIAN PEMBIAYAAN BERMASALAH PADA BANK SUMUT KCP SYARIAH RANTAUPRAPAT - Putri Anggraini; Muhammad Ali Al Ihsan; Ritonga, Mulkan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze the restructuring mechanism in the settlement of non-performing financing at Bank Sumut KCP Syariah Rantauprapat This research uses a qualitative method to collect and analyze data. The primary data source was obtained directly from the research location at Bank Sumut KCP Syariah Rantauprapat. In addition, secondary data is also collected in the form of documents. Data collection was carried out through three methods, namely observation, interviews, and document studies. Thus, this study can obtain a more complete and accurate picture of the phenomenon being studied. The results of the study show that Bank Sumut KCP Syariah Rantauprapat has implemented a restructuring mechanism in accordance with the principles stipulated in Bank Indonesia Regulation (PBI) No. 10/18/PBI/2008 and the circular letter of the board of directors No. 092/Dir/DUSy-PuiB/SE/2019. This mechanism includes three main principles, namely rescheduling, reconditioning, and restructuring. Thus, Bank Sumut KCP Syariah Rantauprapat has shown a commitment to resolving problematic financing in an effective manner and in accordance with applicable regulations. The implementation of this restructuring has proven to be effective in reducing the level of non-performing financing. The main obstacles in the restructuring process are administrative completeness and difficulties in reaching customers who have changed domiciles.